A Systems Approach in the Evaluation and Comparison of Engineering Services Applied in Facilities Management - Halim , Tony; Kanesan , Muthusamy; Sie , Yong Chia; Shao , Wei Lam (2011)

(untitled)
Purpose - This paper is a balance mixed management and engineering concepts which aims to fuse classical engineering methodologies into a systems engineering framework to systematically and comprehensively assess and compare services rendered by engineering systems.